Association of depression, anxiety and quality of life in patients with diabetes mellitus: a systematic review - Maghrabi, Roaa I.; Al-Otaibi, Abeer Bakheet (International Journal Of Community Medicine And Public Health, 2026)
Diabetes mellitus (DM) is frequently associated with psychological comorbidities such as depression and anxiety, both of which may adversely affect quality of life (QoL). This systematic review aimed to evaluate the association between depression, anxiety, and QoL among patients with DM. A systematic literature search was conducted in PubMed/MEDLINE, Google Scholar, DOAJ, and the Cochrane Library according to PRISMA 2020 guidelines. Only studies that used validated instruments to measure depression, anxiety, and QoL in adult patients with type 1 or type 2 DM were included. Data extraction and risk-of-bias assessment were performed independently by two reviewers using ROBINS-I and RoB 2 tools. A total of 17 studies with 45 to 5,259 participants were included. The rate of depression varied from 8% to 57.8% and the rate of anxiety varied from 9% to 57.9%. QoL scores were consistently reported as being significantly negatively related to depression and anxiety across studies. Included data demonstrated strong negative correlations between wellbeing scores and depression (p=-0.579) and anxiety (p=-0.632). Significant inverse correlations between depression and QoL (r=-0.690, p<0.001) and anxiety and QoL (r=-0.646, p<0.001) were also observed. Many studies indicated that the combination of depression and anxiety was linked to physical, psychological, and social impairments. A reduction in depressive and anxiety symptoms was associated with improvement in the dimensions of QoL in intervention studies. There is a strong correlation between depression and anxiety with patient QoL in individuals with diabetes, highlighting the need to incorporate psychological assessment and mental health management into general diabetes care.